ANALYSIS OF VALUE-ADDED PRODUCT AND ECONOMIC VALUE FROM CASSAVA WASTE EXISTENCE IN PEUYEUM ABBAS SAWARGI COMPANY IMPLEMENTATION : CIRCULAR ECONOMY CONCEPT - Sidiq, Reza Nur; Handayati, Yuanita (Journal of Business and Management, 2018)
Abstract.The problem of cassava waste generates aesthetics disruption, health disruption, and also fungi and bacteria, oxygen depletion, and the death of aquatic creatures or biotic life disruption. Besides, the company will lose economic value because they can’t handle it well. Circular economy is an appropriate concept to solve the problem of waste which one of the objective is to generate economic value. Therefore, this study aims to find out how the concept is implemented and also how much economic value can be generated from all cassava waste. The result shows that the implementation of concept in the company has several steps are waste collection refers to all cassava waste were identified will be gathered by the company as raw material that used to produce value-added product, analysis of value-added products aims to find out what products can be made with its economic value, product creation refers to an activity of producing identified value-added product which means there has been the availability of the product. and collaborate with farmers where the company will offer their value-added product to farmers in order to generate benefit by purchasing the product or reselling it to the consumers. Besides, economic value that the company can gain from all cassava waste is Rp98,983,400 per month.Keywords: cassava waste, circular economy, economical value, fermeted-cassava, value-added product